Effect of Replacement of Barley Grains by Wasted Bread Crumbs or Rejected Dates on Growth Performance and Carcass Traits of Growing Rabbits - AL-Shami, S.A.; Mohammed, T.A. (Pakistan Journal of Nutrition, 2009)
Thirty five 10 weeks of age white New Zealand rabbits were assigned to investigate the effect of partial and complete replacement of barley grains by Wasted Bread Crumbs (WBC) or Rejected Dates (RD) on growth performance and carcass traits of growing rabbits. The rabbits were allotted into seven groups (5 rabbits per each). Seven diets were formulated, the control (No. 1) based on barley grains as the main energy source and the tested alternative energy sources (WBC and RD) replaced 33.33, 66.66 and 100% from the barley quantity of the control to formulate 6 diets respectively. The diets were offered for 40 days. The results indicated that WBC inclusion (15 or 30%) reduced (p>0.05) body weight, Daily Body Gain (DBG), Daily Feed Intake (DFI) and deteriorated Feed Conversion (FCR), Protein Efficiency Ratio (PER) and Efficiency of Energy Utilization (EEU) when compared with control, however, the higher inclusion level of WBC reduced (p<0.05) DBG and improved FCR, PER. On the other hand, RD addition at different levels decreased (p<0.05) DBG, increased DFI and deteriorated (p<0.05) FCR, PER, EEU and PI when compared with the control. The data revealed that WBC was more efficient, resulted in good and higher growth performance and rabbits utilized it better than RD. Both WBC and RD reduced dressing % and increased head and viscera relative weights when compared with the control while, WBC reduced (p>0.05) abdominal fat relative weight and RD increased (p>0.05) abdominal fat relative weight. Both WBC and RD had no effect on chemical composition of rabbit’s meat. The data indicated that WBC posses good energy source at different levels for rabbit feeding while RD were less fit and require further investigation.